Learn Android App development - Jackson, Wallace (Apress Imprint: Apress, 2013)
Learn Android App Development is a hands-on tutorial and useful reference. You'll quickly get up to speed and master the Android SDK and the Java that you need for your Android Apps. The Android SDK offers powerful features, and this book is the fastest path to mastering them-and the rest of the Andorid SDK-for programmers with some experience who are new to Android smartphone and tablet apps development. Many books introduce the Android SDK, but very few explain how to develop apps optimally. This book teaches both core Java language concepts and how to wisely but rapidly employ the design patterns and logic using the Android SDK, which is based on Java APIs. You'll also learn best practices that ensure your code will be efficient and perform well. Get an accelerated but complete enough treatment of the fundamentals of Java necessary to get you started. Design your first app using prototyping and other design methods. Build your first Android app using the code given over the course of the book. Finally, debug and distribute your first app on Google Play or other Android app store. After reading this book, you'll have your first app ready and on the app store, earning you the prestige and the money you seek.